A rare presentation of concurrent onset and coexistence of generalized lichen planus and psoriasis in a child - Sunmeet Sandhu; Preema Sinha; Divya Shelly; Siddharth Bhatt (Wolters Kluwer Medknow Publications, 2020)
Independently, psoriasis and lichen planus (LP) are common inflammatory skin conditions affecting around 2-3% and 1% of the population, respectively. However, the coexistence of both diseases is rare. Common immunological mechanisms with altered T-cell-mediated autoimmunity, cytokine milieu, and Koebner phenomenon play a role in their pathogenesis. As reviewed in the literature, psoriasis may independently be associated with other autoimmune conditions like vitiligo, alopecia areata, LP, and discoid lupus erythematosus. A rare co-occurrence of these two or three autoimmune diseases has been reported. Here, we report a case of a 10-year-old boy who presented with persistent nonpruritic multiple hyperpigmented scaly papules and plaques over the body since 6 months of age. Histopathology revealed features suggestive of both LP and psoriasis in the same section. A diagnosis of psoriasis-LP overlap was made, and the patient was managed with tab acitretin 25 mg daily and narrowband ultraviolet B (NBUVB) phototherapy with which he showed satisfactory clearance of the lesions.